2002
DOI: 10.1074/jbc.m200636200
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-2 but Not Thioredoxin-1 Is a Substrate of Thioredoxin Peroxidase-1 from Drosophila melanogaster

Abstract: As Drosophila melanogaster does not contain glutathione reductase, the thioredoxin system has a key function for glutathione disulfide reduction in insects (Kanzok, S. M., Fechner, A., Bauer, H., Ulschmid, J. K., Mü ller, H. M., Botella-Munoz, J., Schneuwly, S., Schirmer, R. H., and Becker, K. (2001) Science 291, 643-646). In view of these unique conditions, the protein systems participating in peroxide metabolism and in redox signaling are of special interest. The genes for a second thioredoxin (DmTrx-2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 38 publications
(39 reference statements)
1
29
0
Order By: Relevance
“…With the thioredoxindependent peroxidase activity assay we showed that the PRX5-like protein reduces H 2 O 2 only in the presence of a functional thioredoxin system. Furthermore, the kinetic parameters of this enzyme for H 2 O 2 are in agreement with activities of a human thioredoxin peroxidase, a thioredoxin peroxidase from Plasmodium falciparum, and a thioredoxin peroxidase-1 from Drosophila melanogaster (52)(53)(54). This led us to conclude that the identified PRX5-like protein is a functional thioredoxin-dependent peroxidase in A. nidulans.…”
Section: Discussionsupporting
confidence: 58%
“…With the thioredoxindependent peroxidase activity assay we showed that the PRX5-like protein reduces H 2 O 2 only in the presence of a functional thioredoxin system. Furthermore, the kinetic parameters of this enzyme for H 2 O 2 are in agreement with activities of a human thioredoxin peroxidase, a thioredoxin peroxidase from Plasmodium falciparum, and a thioredoxin peroxidase-1 from Drosophila melanogaster (52)(53)(54). This led us to conclude that the identified PRX5-like protein is a functional thioredoxin-dependent peroxidase in A. nidulans.…”
Section: Discussionsupporting
confidence: 58%
“…It is possible that these 21 additional differentially expressed genes are unrelated to the resistance phenotype. It is interesting to note that several of them are putatively involved in the oxidative stress response (superoxide dismutases (SOD) [33; 34; 35], thioredoxins (TRX) [36], glutathione-S-transferases (GSTs) [37; 38; 39].…”
Section: Discussionmentioning
confidence: 99%
“…All standard assays were carried out at 25°C. Recombinant N-terminally His-tagged DmTrx-2 was prepared as described (18). NADPH was from Biomol (Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of Cys-Sec mutants were determined from the selenium concentration as measured by atomic absorption spectroscopy (see Table 1). The concentration of oxidized DmTrx-2, purified as described earlier (18), was measured enzymatically by end-point determination by using excess NADPH and 1 unit͞ml of wild-type DmTrxR.…”
Section: Methodsmentioning
confidence: 99%